Fine‐Mapping of SNCA in Rapid Eye Movement Sleep Behavior Disorder and Overt Synucleinopathies. Issue 4 (12th February 2020) - Krohn, Lynne; Wu, Richard Y. J.; Heilbron, Karl; Ruskey, Jennifer A.; Laurent, Sandra B.; Blauwendraat, Cornelis; Alam, Armaghan; Arnulf, Isabelle; Hu, Michele T. M.; Dauvilliers, Yves; Högl, Birgit; Toft, Mathias; et al.
Abstract : Objective: Rapid eye movement sleep behavior disorder (RBD) is a prodromal synucleinopathy, as >80% will eventually convert to overt synucleinopathy. We performed an in‐depth analysis of the SNCA locus to identify RBD‐specific risk variants. Methods: Full sequencing and genotyping of SNCA was performed in isolated/idiopathic RBD (iRBD, n = 1, 076), Parkinson disease (PD, n = 1, 013), dementia with Lewy bodies (DLB, n = 415), and control subjects (n = 6, 155). The iRBD cases were diagnosed with RBD prior to neurodegeneration, although some have since converted. A replication cohort from 23andMe of PD patients with probable RBD (pRBD) was also analyzed (n = 1, 782 cases; n = 131, 250 controls). Adjusted logistic regression models and meta‐analyses were performed. Effects on conversion rate were analyzed in 432 RBD patients with available data using Kaplan–Meier survival analysis. Results: A 5′‐region SNCA variant (rs10005233) was associated with iRBD (odds ratio [OR] = 1.43, p = 1.1E‐08), which was replicated in pRBD. This variant is in linkage disequilibrium (LD) with other 5′ risk variants across the different synucleinopathies. An independent iRBD‐specific suggestive association (rs11732740) was detected at the 3′ of SNCA (OR = 1.32, p = 4.7E‐04, not statistically significant after Bonferroni correction). Homozygous carriers of both iRBD‐specific SNPs were at highly increased risk for iRBD (OR = 5.74, p = 2E‐06). The known top PD‐associated variant (3′ variant rs356182) had an opposite direction of effect in iRBD compared to PD. Interpretation: There is a distinct pattern of association at the SNCA locus in RBD as compared to PD, with an opposite direction of effect at the 3′ of SNCA . Several 5′ SNCA variants are associated with iRBD and with pRBD in overt synucleinopathies. ANN NEUROL 2020;87:584–598